Anjangsana as Cultural Infrastructure: Social Capital and Turath Literacy in Situbondo - Abdi, Efan Chairul; Hidayat, Ahmad Fadhel Syakir (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2026)
Anjangsana Ihya’ in Situbondo constitutes a socio-cultural practice that sustains the continuity of community-based turāth learning. This topic is important because studies of kitab kuning are often confined to institutional settings, whereas the mechanisms through which non-formal adult practices integrate ritual, social relations, and community governance remain underexplored. This study employs a qualitative ethnographic approach, drawing on participant observation, in-depth ethnographic interviews with key actors (shaikhs, qāri’ [readers], mustami’ [active listeners], technical organizers, hosts, and students), and documentation (schedules, field notes, and WhatsApp group communications). Data analysis follows Spradley’s stages (domain, taxonomic, componential, and cultural theme analyses). The findings indicate that Anjangsana Ihya’ operates as a rotating community event (homes, mosques, and public venues) with a stable format: ritual opening (tawassul and al-Fātiḥah), rotating readings, collective meaning negotiation, ritual closing (tahlīl and supplication), and a social phase of hospitality. Continuity is maintained through a structured role ecology, ritual framing, layered hospitality, and WhatsApp-based hybrid governance that coordinates schedules and extends discussion beyond meetings. The practice contributes to social capital (trust, shared norms, and reciprocity) and cultural reproduction through turāth literacy, cross-edition textual verification, and the reinforcement of values such as adab, khidmah, and intergenerational togetherness. Overall, the findings position Anjangsana Ihya’ as “cultural infrastructure” that keeps turāth learning alive while strengthening community cohesion.